Nurse's Knowledge, Attitude, and Practice Toward Pressure Ulcer Prevention at the University of Science and Technology Hospital and Al-Gumhori Hospital, Sana'a, Yemen, 2025 - Al-Salahi, Hashem Ameen; Harhara, Malek Fayz; Saadan, Taha Khalid; Al-Ahdal, Hassan Thabet; Zubair, Honain Mansour; Al-Humaidi, Hudaifa Jameel (My University, 2025)
Background: Pressure ulcers are a significant cause of patient morbidity and healthcare burden worldwide. Effective prevention largely depends on nurses' knowledge, attitudes, and practices (KAP), yet gaps between knowledge and clinical practice have been reported. Aim: To assess the levels of knowledge, attitude, and practice among nurses regarding pressure ulcer prevention in two hospitals in Al-Gumhori and the University of Science and Technology Hospitals in Sana'a, Yemen.